Continued sex-differences in the rate and severity of knee injuries among collegiate soccer players: The NCAA injury surveillance system, 2004-2009 - Fulstone, D.; Chandran, A.; Barron, M.; DiPietro, L. (International Journal of Sports Medicine, 2016)
We extend previous analyses and examined sex-differences in the rate and severity of knee injuries among collegiate soccer players between 2004 and 2009. Data from the National Collegiate Athletic Association Injury Surveillance System (NCAA ISS) were used to calculate injury incidence density (ID) per 1?000 athletic exposures (AE). Multivariable regression modeling then tested the relation between sex and knee injury incidence and severity among all injured soccer players, while controlling for contact, setting, and division level, as well as for the interactions among these variables. The rate of knee injuries was 1.19 per 1?000 AEs in women and 0.91 per 1?000 AEs in men (RR=1.31, 95% Wald CI=[1.16, 1.47]). In the multivariable modeling, women continued to experience significantly higher odds of knee injury compared with men (aOR=1.44, 95% CI=[1.27,1.63]). Also, the adjusted odds of a knee injury that resulted in surgery remained higher in women compared with men (aOR=1.61 (1.00, 2.58), as well as the amount of time lost from participation (beta=0.129; p=0.05). Given the prominence of soccer play in the United States, continued efforts to evaluate and improve knee injury prevention practices and policies may be especially important for female players